Azimuthal P–P prestack seismic prediction of fractures for superdeep carbonate reservoirs in northwest China. (March 2022) - Li, Zongjie; Fu, Li-Yun; Liu, Jun; Wang, Zhiwei; Jian, Shikai
Abstract: Ordovician fractured carbonates under study are over 7000 m deep in northwest China. Multistage tectonic activities result in numerous fractures along the strike-slip faults, accompanied with karst collapses due to atmospheric freshwater seepage. The resultant cave-fracture system provides numerous channels favorable for the migration and storage of hydrocarbons. Azimuthal anisotropy analyses with wide-azimuth and high-density 3D seismic data facilitate fracture estimation from migrated CRP gathers in this area. Compared with azimuthal velocity variations, azimuthal amplitude variations are quite sensitive to fractures, but suffer many negative factors. Major difficulties with azimuthal amplitudes to map superdeep fractured reservoirs include non-uniform distribution of azimuths and offsets, extremely low S/N ratio (SNR), anisotropic effect of strike-slip faults, and shielding effect of overlying irregular igneous strata. We propose an integrated scheme with azimuthal P–P amplitude/frequency attributes for prestack prediction of fractures based on the migrated CRP gathers. First, we analyze the distribution of azimuths, offsets, and bins to identify appropriate bins with the best range of offsets and the uniform distribution of azimuths. The selected wide-azimuthal CMP gathers are regrouped in terms of five azimuths, followed by azimuthal prestack migration. The resulting subazimuthal CRP gathers are optimized by denoising, flattening by residual static correction, and wavelet shaping to improve both SNR and resolution. We then conduct a local stacking in 100 m × 100 m bin for the best range of offsets from 1000 to 5600 m, followed by matched filtering to remove the footprint effect of overlying igneous strata. Frequency-related amplitude attributes are extracted for sensitive analyses in azimuths by ellipse fitting, yielding several optimal attributes for fracture prediction. We demonstrate that the coupled amplitude and frequency attributes in terms of energy percentages are the best in this area. Case studies show the applicability of the presented scheme for detecting superdeep fracture sets from extremely low SNR seismic data. Highlights: A complete processing workflow is proposed, which provides reliable basic data for prestack fracture prediction. We analyze the effects of azimuths, offsets, bins, and folds for wide-azimuth and high-density 3D seismic acquisition, which ensure that the offsets and azimuths. Frequency-related amplitude attributes are extracted in the azimuthal P–P migrated CRP gathers for sensitive analyses in azimuths by ellipse fitting. Our method has a good applicability to the detection of superdeep fracture sets from extremely low SNR seismic data.